The NBN Futures Project - Holmes, Jim; Campbell, Leith (Journal of Telecommunications and the Digital Economy, 2020)
Over the past 20 years the provision of broadband services in Australia has become a matter of contention. The National Broadband Network (NBN) and longer-term plans for the way in which it will be structured and operate into the future have been caught up in this. The potential sale by the government of NBN Co, the developer of the NBN, in the next few years has brought greater urgency to considering the longer-term future of the NBN.An NBN Futures Project, whose aims are explained in this article, is promoting public and policy discussion through TelSoc (the Telecommunications Association) on the NBN and its future, with the aim of building consensus and common ground as a basis for developing public policy for the future. TelSoc’s role is not to advocate particular policy positions, but to provide media and forums for ensuring that critical analysis and discussion does occur and is shared as widely as possible. The Project promotes articles in the Journal of Telecommunications and the Digital Economy, together with forums, talks and other events.This article describes the NBN Futures Project and how it envisages that it will make a difference.